Environment and storage period for conservation of surinam cherry seeds (Eugenia uniflora L.) - Garay, Igor; da Rosa, Viviane; Felipe de Miranda Siminihuk, Lucas; Wagner Junior, Américo (Comunicata Scientiae, 2025)
The Surinam cherry tree is a native Brazilian fruit tree with potential for use in several segments. Normally, it is propagated by seeds, but its biggest obstacle is the fact that it is recalcitrant, making its germination capacity unviable if stored in an unsuitable environment. The objective of this work was to evaluate the viability of Surinam cherry seeds stored under natural environmental conditions and freezing and cooling temperatures, in three different packages (ziplock, kraft paper and vacuum) during nine periods (0, 5, 10, 15, 20, 25, 30, 60 and 90 days). The study was carried out at UTFPR - Campus Dois Vizinhos. The experimental design used was completely randomized, adopting analysis for each type of packaging in a 3 x 9 factorial scheme (storage temperature x period), with four replications of 50 seeds per experimental unit. The germination, germination speed index and average germination time were analyzed. According to the results, the Surinam cherry seeds lost their viability in Kraft paper, vacuum and ziplock packaging from the thirtieth day onwards when kept in natural and cooling conditions. The seeds did not tolerate the use of freezing temperatures, regardless of the maintenance period. Under natural conditions, using Kraft paper packaging, germination remained above 40% up to five days, different from other environments, in which vacuum and ziplock remained up to 15 days in natural conditions and, from 25 to 30 days under cooling, respectively.